Greater Gains in Spine and Hip Strength for Romosozumab Compared With Teriparatide in Postmenopausal Women With Low Bone Mass - Keaveny, Tony M.; Crittenden, Daria B.; Bolognese, Michael A.; Genant, Harry K.; Engelke, Klaus; Oliveri, Beatriz; Brown, Jacques P.; Langdahl, Bente L.; Yan, Chris; Grauer, Andreas; Libanati, Cesar (Journal of Bone and Mineral Research, 2017)
Romosozumab is a monoclonal antibody that inhibits sclerostin and has been shown to reduce the risk of fractures within 12 months. In a phase II, randomized, placebo-controlled clinical trial of treatment-naïve postmenopausal women with low bone mass, romosozumab increased bone mineral density (BMD) at the hip and spine by the dual effect of increasing bone formation and decreasing bone resorption. In a substudy of that trial, which included placebo and teriparatide arms, here we investigated whether those observed increases in BMD also resulted in improvements in estimated strength, as assessed by finite element analysis. Participants received blinded romosozumab s.c. (210 mg monthly) or placebo, or open-label teriparatide (20 μg daily) for 12 months. CT scans, obtained at the lumbar spine (n = 82) and proximal femur (n = 46) at baseline and month 12, were analyzed with finite element software (VirtuOst, O.N. Diagnostics) to estimate strength for a simulated compression overload for the spine (L1vertebral body) and a sideways fall for the proximal femur, all blinded to treatment assignment. We found that, at month 12, vertebral strength increased more for romosozumab compared with both teriparatide (27.3% versus 18.5%; p = 0.005) and placebo (27.3% versus -3.9%; p < 0.0001); changes in femoral strength for romosozumab showed similar but smaller changes, increasing more with romosozumab versus teriparatide (3.6% versus -0.7%; p = 0.027), and trending higher versus placebo (3.6% versus -0.1%; p = 0.059). Compartmental analysis revealed that the bone-strengthening effects for romosozumab were associated with positive contributions from both the cortical and trabecular bone compartments at both the lumbar spine and hip. Taken together, these findings suggest that romosozumab may offer patients with osteoporosis a new bone-forming therapeutic option that increases both vertebral and femoral strength within 12 months. © 2017 American Society for Bone and Mineral Research.
EVALuna2:33269